Is citizenship the answer? Constructions of belonging and exclusion for the stateless Rohingya of Burma - Pugh, C (International Migration Institute, 2013)
The Rohingya, a Muslim ethnic minority group in Arakan State, Burma, are among the most vulnerable and persecuted populations across the globe. Despite their significant historical presence in the country, the Government of Burma does not recognise the Rohingya as citizens, thus rendering the population stateless. Many observers argue that the root cause of the crisis is the group’s denial of legal status, suggesting that granting them citizenship would offer a lasting solution. While the possession of legal status is fundamental to an inclusive notion of citizenship, consideration of other non-formal dimensions of citizenship are just as necessary in expanding the boundaries of inclusion. Drawing on the case of the Rohingya, I will conduct a genealogy of exclusion to illustrate that their status is not merely a product of lacking citizenship, but rather embedded in more elaborate processes of nation building, ethno-political identification, and religious intolerance. This paper challenges the centrality of the concept of legal citizenship through an interrogation of the Rohingya’s exclusion from historical narratives, their ambiguous status, and their current socioeconomic insecurity in an attempt to move the conversation beyond their statelessness and lack of formal status to understand the true nature of their exclusion.